LONELINESS AND SOCIAL ISOLATION AS CLINICAL RISK FACTORS IN PRIMARY CARE: A COMPREHENSIVE REVIEW OF CARDIOVASCULAR, MENTAL HEALTH, AND MORTALITY OUTCOMES - Hamad Abdulaziz AlSubaie; Abdullatif Mohammed Al Joher (World Journal of Biology Pharmacy and Health Sciences, 2026)
Background: Loneliness and social isolation have emerged as central concerns in contemporary preventive medicine. Once considered predominantly social or psychological phenomena, they are now recognized by the World Health Organization and the United States Surgeon General as pressing public health priorities with measurable biological consequences. Their prevalence has risen sharply in the wake of demographic ageing, family fragmentation, urbanization, and the COVID-19 pandemic, positioning primary care clinicians at the front line of detection and management. Objective: This review synthesizes contemporary epidemiological, mechanistic, and clinical evidence on loneliness and social isolation as independent risk factors for cardiovascular disease, adverse mental health outcomes, and all-cause mortality, and evaluates the implications for routine primary care practice. Methods: A structured narrative review was conducted of peer-reviewed meta-analyses, prospective cohort studies, Mendelian randomization analyses, mechanistic laboratory work, and international policy statements published between 2010 and 2025, retrieved from PubMed, the Cochrane Library, and the archives of major cardiology, psychiatry, and public health journals. Results: Convergent evidence from more than two dozen high-quality investigations indicates that social disconnection independently increases the risk of coronary heart disease by approximately 29%, stroke by 32%, incident heart failure by 15–20%, type 2 diabetes by 20–33%, dementia by roughly 31%, and all-cause mortality by 22–32%, with hazard ratios comparable to those of established risk factors such as smoking, obesity, and physical inactivity [5–10]. Mechanistic work implicates hypothalamic–pituitary–adrenal axis dysregulation, chronic low-grade inflammation, up-regulation of the conserved transcriptional response to adversity, sympathetic overactivation, impaired sleep architecture, and adverse health behaviours . Brief screening tools such as the three-item UCLA Loneliness Scale can be integrated into routine consultations, and structured non-pharmacological interventions, including cognitive-behavioural therapy and link-worker–delivered social prescribing, demonstrate measurable reductions in loneliness scores. Conclusion: Loneliness and social isolation warrant recognition as modifiable clinical risk factors in primary care. Their systematic identification, biopsychosocial contextualization, and integration into cardiovascular and mental health risk-reduction pathways constitute an ethical and empirical imperative for the coming decade.